Soil structure and microbial activity dynamics in 20‐month field‐incubated organic‐amended soils. (9th January 2014) - Arthur, E.; Schjønning, P.; Moldrup, P.; Razzaghi, F.; Tuller, M.; De Jonge, L. W.
Summary Soil structure formation is essential to all soil ecosystem functions and services. This study aims to quantify changes in soil structure and microbial activity during and after field incubation and examine the effect of carbon, organic amendment and clay on aggregate characteristics. Five soils dominated by illites, one kaolinitic soil and one smectitic soil were sieved to 2 mm, and each soil was divided into two parts and one part amended with ground rape shoots (7.5 t ha−1) as an organic amendment. Samples were incubated in the field for 20 months with periodic sampling to measure water‐dispersible clay (WDC) and fluorescein diacetate activity (FDA). After incubation, WDC and FDA were measured on air‐dried 1–2‐mm aggregates. Tensile strength was measured on four aggregate classes (1–2, 1–4, 4–8 and 8–16 mm) and results used to assess soil friability and workability. Intact cores were also sampled to determine compressive strength. During incubation, the amount of WDC depended on soil carbon content while the trends correlated with moisture content. Organic amendment only yielded modest decreases (mean of 14% across all sampling times and soils) in WDC, but it was sufficient to stimulate the microbial community (65–100% increase in FDA). Incubation led to significant macroaggregate formation (>2 mm) for all soils. Friability and strength of newly‐formed aggregates were negatively correlated with clay content and carbon content, respectively. Soil workability was best for the kaolinite‐rich soil and poorest for the smectite‐rich soil; for illitic soils, workability increased with increasing organic carbon content. Organic amendment decreased the compression susceptibility of intact, incubated samples at smaller stress values (<200 kPa).